Bioaccumulation of cadmium and thallium in Pb-Zn tailing waste water by Lemna minor and Lemna gibba - Sasmaz, Merve; Obek, Erdal; Sasmaz, Ahmet (Pergamon-Elsevier Science Ltd, 2019)
The present study investigated the removal ability to phytoremediate cadmium and thallium from tailing waste water of Lemna gibba and Lemna minor. These plants were separately adapted to the reactors, placed in the water and daily collected during the eight days. During the study, the plant and water samples were taken daily and the pH, temperature and electric conductivity of the tailing waste water were daily measured in situ. L. minor and L. gibba were firstly washed, dried in and then ashed at 300 degrees C for 24 h in an oven. Both ashed plant and water samples were analyzed by ICP-MS to find out the concentrations of cadmium (Cd) and thallium (Tl). Although Cd and Tl are at low values (11.4 +/- 0.5 mu g L-1 for Cd and 2.85 +/- 0.5 mu g L-1) in tailing waste water, the Cd and Tl were accumulated at the highest amounts by L. minor (31.08 mg L-1 for Cd and 13.43 mg L-1 for Tl) and L. gibba (38.9 mg L-1 for Cd and 17.18 mg L-1 for Tl). Our study on the fourth day showed that L. minor accumulated more removal abilities of Cd (94.56 times) and Tl (7.33 times) than in L. gibba L. (25.89 times on the third day for Cd and 6.16 times on the fourth day for Tl) but L. gibba accumulated higher Cd and Tl concentrations (38.9 mg Cd kg(-1)and 17.18 mg Tl kg(-1)) than in L. minor. Therefore, these plants can use to remove Cd and Tl in tailing waste water polluted by Cd and Tl.
Keywords: Accumulation; Lemna gibba; Lemna minor; Cadmium; Thallium; Tailing waste water; Keban